A new model for studying deep partial-thickness burns in rats - Guo, Hui-Fang; M. Ali, Razana; A. Hamid, Roslida; A. Zaini, Asma; Khaza’ai, Huzwah (e-Century Publishing Corporation, 2017)
Burn injuries are one of the most devastating injuries in the world. A uniform burn wound is essential for burn research. The objective of this study was to describe a new model for inducing deep partial-thickness burns in rats. Burn wounds were performed on the dorsal part of Sprague-Dawley rats using a constructed heating device in our laboratory. Digital images of each animal were captured every day for macroscopic evaluation and for assessment of the wound contraction rate. Six animals were sacrificed on days 1, 3, 7, 11, 14, and 21 after onset of burn and their skin tissues were harvested for histological analysis. Uniform deep partial-thickness burns could be achieved in Sprague-Dawley rats under the condition of a contact temperature of 70°C, with the weight of heating devices of 300 g, and a duration of 10 s. Macroscopic evaluation recorded the general appearance of the deep partial-thickness burns. Evaluation of the wound contraction rate showed that the deep partial-thickness wound area was reduced by 90.39% of the original wound area by day 21 after burn. Microscopic evaluation by hematoxylin-eosin staining revealed the histological changes during the wound healing process. This is a standardized and reproducible model for inducing deep partial-thickness burns in Sprague-Dawley rats.